PREACHING AT YOUR FINGERTIPS: BUILDING DIGITAL LITERACY ON THE ISLAMIC CHARACTER OF MAHMUDAH (CHARISM) OF GEN Z - Sofia Fahrany (Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2025)
This research is motivated by the problem of the Development of digital technology that has changed the way humans interact, communicate, and obtain information, including in the field of Islamic da'wah. The findings of Generation Z's problems as a digital native generation, namely: 1. Facing significant challenges in the form of massive information flows, hoaxes, 2. Harmful content from Lesbian, Gay, Bisexual, Transgender (LGBT) that is contagious for the character formation of Gen Z, 3. Degradation of moral values ??, such as violence and intimacy, in the digital space. Therefore, da'wah in the digital era not only serves as a medium for conveying religious messages but also as a means of fostering digital literacy grounded in the character of Mahmudah Islam (charisma). This study aims to analyze the role of digital da'wah in building digital literacy oriented towards the formation of Mahmudah Islamic character in Generation Z. The research method used is a qualitative approach with literature studies on scientific sources, journals, and relevant works such as the book on the transformation of Islamic Religious Education (PAI) in the digital era, theory, practice and challenges (QRISET, 2025). The results of the study show that effective digital preaching can increase critical awareness, media ethics, and internalisation of noble moral values ??such as honesty, responsibility, manners, and religious moderation. Thus, da'wah at your fingertips becomes a strategic instrument in shaping a digitally savvy Generation Z with a compassionate Islamic character.